(untitled) (Journal of Environmental Science Studies, 2023)
The proposed area for establishment of Phu Yen Geopark is limited to 6 districts, towns and cities, including: Tuy Hoa City, Dong Hoa provincial town, Tuy An district, Song Cau provincial town and 3 communes, 1 town in Phu Hoa district town, 3 communes in Son Hoa district with an area of 1,575 km2. Distributed in the central coastal line, the area’s topography is quite diverse, including mountains, hills, plains and coastal areas, divided into 6 main origin types: 1) Terrain tectonics, volcanoes, architectural erosion, include: The tectonic and cavitation flanks of Pliocene - Quaternary age; Highland ridge, Neogene - highland Quaternary; Surface of the volcanic plateau has an elevation of less than 250 m; Surface of volcanic plateau is 300-400 m high; Cone ridge of Quaternary age crater; Structural eroded slope; Slope erodes edge of dome of the intrusive blocks, quartz fracture zones; 2) Terrain formed by erosion – cavitation, include: Pediple leveled surface, Miocene age 750 - 1100m high; Pediple leveled surface, early Pliocene age 450 - 600 m high; Pediple leveled surface, late Pliocene age 300 – 400 m high; Pediment leveled surface, Late Pliocene - Early Pleistocene age 150 - 250m high; Early - middle Pleistocene pedimen surface, 50 - 120 m high; Cavitation flank; Cavitation flanks of crevices and ditches of Quaternary age; Cavitation – erosion flanks; Collapsed erosion flank in Neogene - Quaternary age; Synthetic erosion flank Neogene - Quaternary age; Abrasion flank Quaternary age; 3) Terrain formed by rivers, include: River shelf level II, late Pleistocene age; River shelf level I, middle Holocene age; River accumulation delta, late Holocene age, early age; River bed and low alluvial ground along the riverbed, late Holocene age, late age; 4) Terrain formed by the sea, include: Abrasion – marine accumulation surface, Early – Middle Pleistocene age; Abrasive seashelf – accumulation level III, late Pleistocene age, early age; Abrasive seashelf – accumulation level II, late Pleistocene age, late age; Sea shelf level I, middle Holocene age, 5-10 m high; Surface of the sand dyke connecting the island, late Holocene age, early age; Modern beaches are flooded with frequent tides; 5) Terrain include:formed by the mixed impact of rivers and sea, include: The river-sea delta (shelf) of the Late Pleistocene age, Late and Middle Holocene age; Modern sea-swamp plain; Modern river-swamp plain; 6) Terrain formed by wind, include: Terrain type of sand dunes with elevation of 15-25 m; The terrain is sandy hill with an altitude of 105 m. Each terrain type is associated with diverse geological heritages: paleontological heritage; geomorphological heritage; stone heritage…